Cyanidin attenuates the apoptosis of rat nucleus pulposus cells and the degeneration of intervertebral disc via the JAK2/STAT3 signal pathway in vitro and in vivo - Xiaoliang Bai; Meichao Jiang; Jie Wang; Shuai Yang; Zhiwei Liu; Hongxin Zhang; Xiaojuan Zhu (Taylor & Francis Group, 2022)
Context Cyanidin has been shown to have therapeutic potential in osteoarthritis. However, it is unclear whether cyanidin prevents the progression of intervertebral disc degeneration (IVDD). Objective This study evaluates the effects of cyanidin on IVDD in vitro and in vivo. Materials and methods Nucleus pulposus cells (NPCs) isolated from lumbar IVD of 4-week-old male Sprague-Dawley (SD) rats were exposed to 20 ng/mL IL-1β, and then treated with different doses (0-120 µM) of cyanidin for 24 h. SD rats were classified into three groups (n = 8) and treated as follows: control (normal saline), IVDD (vehicle), IVDD + cyanidin (50 mg/kg). Cyanidin was administered intraperitoneally for 8 weeks. Results The IC50 of cyanidin for NPCs was 94.78 µM, and cyanidin had no toxicity at concentrations up to 500 mg/kg in SD rats. Cyanidin inhibited the apoptosis of NPCs induced by IL-1β (12.73 ± 0.61% vs. 18.54 ± 0.60%), promoted collagen II (0.82-fold) and aggrecan (0.81-fold) expression, while reducing MMP-13 (1.02-fold) and ADAMTS-5 (1.40-fold) expression. Cyanidin increased the formation of autophagosomes in IL-1β-induced NPCs, and promoted LC3II/LC3I (0.83-fold) and beclin-1 (0.85-fold) expression, which could be reversed by chloroquine. Cyanidin inhibited the phosphorylation of JAK2 (0.47-fold) and STAT3 (0.53-fold) in IL-1β-induced NPCs. The effects of cyanidin could be enhanced by AG490. Furthermore, cyanidin mitigated disc degeneration in IVDD rats in vivo. Discussion and conclusions Cyanidin improved the function of NPCs in IVDD by regulating the JAK2/STAT3 pathway, which may provide a novel alternative strategy for IVDD. The mechanism of cyanidin improving IVDD still needs further work for in-depth investigation.